La connaissance du climat au Brésil : entre le vernaculaire et le scientifique - Francisco Mendonça (Confins)
The knowledge of climate in Brazil is the overlap between the vernacular knowledge and the scientific knowledge, although in the context of the academy the scientific and technical approach is predominant. For the greatest part of the population the vernacular knowledge (or traditional) on climate is more important than science. However, in the context of science, the development and consolidation of the brazilian climatology occurred only around the last 70 years. The diffusion of the principle of the dynamic meteorology was one of the main aspects to the development of the study of the brazilian climates. During that period the Brazilian climatology shows advancements and originality, rhythmical analysis of weather and the urban climate studies are the most importants propositions. The environmental question, the satellite images and the debate concerning global changes are the main subjects of interest of the Brazilian climatology in the present time. Some studies related to the perception of climate have recognized the importance of vernacular knowledge about climate in Brazil, inaugurating a new opportunity for science, an approach more open, plural, and richer than strictly modern science.